POTRET SEKTOR UNGGULAN: PEMETAAN POTENSI LOKAL EMPAT KABUPATEN DI MADURA MELALUI TIPOLOGI KLASSEN - Salam, Nurin; Risqi Noor Hidayati Putri (Jurnal Ekonomika : INDEPENDEN, 2024)
During the period from 2015 to 2023, economic growth in the four districts of Madura has been below the average growth rate of East Java Province. This suggests that these districts continue to face significant challenges in driving economic development. To stimulate higher economic growth, the objective is to identify leading sectors based on an analysis using the Tipology Klassen. The research employs a descriptive quantitative approach with secondary data. The findings reveal that several sectors share similar quadrant positions while also highlighting differences in sector potential across Bangkalan, Sampang, Pamekasan, and Sumenep. Keyword: Tipology Klassen, Leading Sector, Madura Island